PRACTICE OF KENYAN LEGAL CODES AND THE EFFECTIVE APPLICATION OF INFORMAL CONTROLS AND SANCTIONS IN MAINTAINING SOCIAL ORDER - Maratu, Gilbert Muriuki (Advances in Social Sciences Research Journal, 2018)
Despite being in existence since immemorial, informal controls and sanctions has never been given due attention in the practice of restoring social order by many legal systems. This is evident by the non recognizance of resolutions made informally by the jurisprudence. This has made many people contempt informal controls and sanctions in checking social misbehaviors. This paper seeks to find out whether the practice of Kenyan legal codes hampers effective application of informal controls and sanctions in maintaining social order in Chiakariga Ward, Kenya. This study employed interview method and structured interview schedule as a tool to collect primary data from 100 respondents and analyzed the collected data using SPSS version 20. This study finding found out that practice of Kenyan legal codes has down played informal controls and sanctions in maintaining social order in Chiakariga Ward. This suggests that informal controls and sanctions conflict with principles of Kenyan legal codes in practice rather than supporting and complementing each other. Study also indicated that aspects of modernization and social structure has made residents of Chiakariga ward shy away from informal practices due to their changed world view points.